Regional trade expansion opportunities in Central and South Asia: exploring trade complementarity, diversification and similarity - Nassir Ul Haq Wani; Afzalur Rahman; Veena Grover; Shoira Mirzakhidova; Mohammad Mirwais Rasa (Cogent Economics & Finance, 2024)
The study investigates the implementation of trade routes and their impact on the regional economic integration of Central and South Asia. It uses three indices, the Trade Complementarity Index (TCI), Similarity Index (SI), and Trade Diversification Index (TDI), to evaluate the level of regional economic integration from 2015 to 2021. The results suggest that the potential trade value in the two regions is twice as significant as the actual level. The study also highlights the importance of various governmental measures to promote and enhance trade and investment within and between the two regions. The study finds a positive correlation between an economy's size and level of development, suggesting that developed economies tend to have higher ratings. Several trade routes have shown advantages in promoting regional trade growth, such as augmenting price competitiveness, facilitating intra-industry trade and examining trade complementarities. The implications of these findings are significant for the effectiveness of trade-related policies, programs and institutional procedures in promoting enhanced trade within and between the two regions. The study contributes to the empirical literature in such a way as to provide (a) practical knowledge and methods for businesses to take advantage of Central and South Asia regional opportunities; (b) analytical tools for policymakers and researchers; and (c) policy and program recommendations for governments and development partners. It should be of interest to businesses, governments, international development partners, policymakers and researchers, and others concerned with Central and South Asia's trade and the potential for developing value chains or so-called 'trade in tasks' across the two regions.
Keywords: F11; F13; F17; 330; South Asia; Central Asia; diversification; trade complementarity; similarity